Pembentukakan Jati Diri Remaja Broken Home Melalui Layanan Konseling Individu Di Desa Karanggungan, Kelurahan Tangkil, Kecamatan Sragen Tahun Pembelajaran 2021 - Brigita Ringgit Wulandi (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
The purpose of this research is to find out how individual counseling services can shape the personality of teenagers from broken families in Karanggungan, Tangkil, Sragen in 2021 academic year. This research was conducted in Tangkil, Sragen in 2021 academic year. This research is a qualitative descriptive research. Collecting data using interview, observation, and documentation techniques. In its implementation, this study involved 2 teenage victims from broken families as research subjects and several other people as informants. While the object of this research is the discovery of the personality of teenagers who were victims of broken families. Data testing is done by using triangulation. While data analysis obtained from data collection, data reduction, data presentation, and drawing conclusions. The results of interviews, observations, and documentation showed that by providing individual counseling services to the teenagers from broken families can help them in finding their personalities. Thus, it can be concluded that the formation of the personality of teenagers from broken families can be done through the provision of individual counseling services. Keywords: Individual Counseling, Adolescent Personality from a broken family